Resolution enhancement in continuous-wave stimulated emission depletion microscopy by excitation beam with modulated vortex-phased azimuthally polarized light. (November 2020) - Lim, Geon; Kim, Wan-Chin; Park, No-Cheol
Highlights: PSF engineering; STED microscopy; Superresolution; fluorescence imaging. Abstract: In this paper, we report an optical system that can effectively enhance the resolution of continuous-wave (CW) stimulated emission depletion (STED) microscopy by applying an amplitude-modulated azimuthally polarized light with vortex phase (AV) as an excitation beam. Based on the vector field diffraction theory, we analyzed electric fields near the focal plane for various polarization states and rotationally symmetric amplitude modulation conditions. From the analysis, it was found that by applying the amplitude modulated AV beam by the ring-shaped blocking aperture, the resolution in the lateral direction can be improved while minimizing the degradation of the resolution in the axial direction. The reported novel excitation method was experimentally verified based on the imaging of gold beads and fluorescent nano-beads. Accordingly, it was confirmed that the lateral resolution was improved by ~20% and the spot elongation in the axial direction was effectively suppressed.